Is Kosova Prepared for Knowledge Economy? Case of Business and Management Students - Rrezehana Hasani Abazi (International School for Social and Business Studies, 2021)
Purpose: This paper examines typical management and business students' attributes and whether they are ready for a knowledge economy. Bearing in mind that education is the key driver of the knowledge economy and business and management fields are significantly impacted by the introduction of the knowledge economy, it is clear why this topic was chosen.  Study design/methodology/approach: The study contributes to knowledge by answering these questions: 'What are the features of a typical business and management student from Kosova?' and 'Do these students have the skills and capabilities to succeed in the knowledge economy?'. To respond to these questions, a questionnaire is compiled and distributed electronically to students. Findings: The findings of this paper are inspiring and encouraging of the prospect of Kosova in coming years. It seems that students are equipped with knowledge, self-confidence and abilities to succeed in this interconnected world. Regarding skills and capabilities to succeed in the knowledge economy, students claim to recognise the importance of lifelong learning, written and oral communication skills, teamwork and creativity. Originality/value: To the authors' knowledge this is the first paper that deals with the knowledge economy in Kosova from the students' perspective.